The concentration of androgens and estrogens in benign prostatic hyperplasia - G. E. Roitberg; K. G. Mkrtchyan; N. G. Kulchenko (Андрология и генитальная хирургия, 2021)
Background. The etiology of benign prostatic hyperplasia (BPH) has not been fully studied. The main role in the induction of prostate tissue proliferation is assigned to the metabolism of testosterone. Recently, it has been reported that one of the risk factors for BPH is a chronic violation of the blood supply to the prostate.The study objective is to determine the level of reproductive hormones in blood serum and prostate tissue when creating a model of chronic ischemia.Materials and methods. The model of chronic pelvic ischemia was created in 10 white non-linear mature rats by partial ligation of the inferior vena cava. The control group of the study consisted of 10 male rats of the same age. After 1.5 months, we performed a hormonal study in all rats (n = 20) determining the concentration of testosterone, dihydrotestosterone and estradiol in the blood and prostate tissue. Also, in all animals (n = 20), a morphological study of the prostate was performed.Results. We’ve found a significant increase in prostate mass in the main group of rats by 16.4 % (p <0.05). Animals with BPH and impaired blood supply to the prostate had changes in their hormonal status: increased levels of testosterone (p <0.05) and dihydrotestosterone (p >0.05) in the prostate tissue.Conclusion. Long-term ischemic disorders in the prostate may be a trigger factor for the development of BPH due to an increase in the concentration of testosterone.